Hydraulic Fracturing and Rock Mechanics - Zhao, Yu.; Zhang, Yongfa; He, Pengfei; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This open access book is the first to consider the effect of non-uniform fluid pressure in hydraulic fractures. The book covers the key topics in the process of hydraulic fracture nucleation, growth, interaction and fracture network formation. Laboratory experiments and theoretical modeling are combined to elucidate the formation mechanism of complex fracture networks. This book is suitable for master$1 (Bs/Ph.D. students, scientists and engineers majoring in rock mechanics and petroleum engineering who need to use a more reliable model to predict fracture behavior.s
1 Introduction -- Part I Laboratory observation -- 2 Rock mechanics in hydraulic fracturing operations -- Part II Laboratory observation -- 3 Reservoir characteristics -- 4 Constant flow injection -- 5 Constant pressure injection -- Part III Theoretical modeling considering Nonuniform fluid pressure -- 6 Fracture initiation -- 7 Fracture propagation -- 8 Fracture interaction behaviors -- Part IV Field implication -- 9 Formation of complex networks -- Epilogue -- References.
Keywords: Geotechnical engineering; Mechanical engineering; Geotechnical Engineering and Applied Earth Sciences; Mechanical Engineering